ANALISIS PENGARUH DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP TINGKAT PERTUMBUHAN EKONOMI DI KABUPATEN SIMEULUE - Murdaya, Jojo; Syahril (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study seeks to analyze the effect of general allocation funds and special allocation funds on the level of economic growth in Semeulue Regency. In this study, quantitative research method was employed. Research sample was determined by using a saturated sample, namely to the entire population. The analysis used by the researcher is descriptive statistical analysis using multiple linear regression. From these results, it is concluded that the general allocation fund and the special allocation fund have a significant effect on economic growth. Multiple regression test resulted in constant -10,055, general allocation fund 1.715, and special allocation fund 4.079. The results of hypothesis testing show that general allocation funds has insignificant effect on economic growth in Simeulue Regency, and special funds have a significant effect of 90.10%, while the remaining 9,90% on economic growth influenced by other variables beyond this study.